2018
DOI: 10.1007/s40071-018-0189-2
|View full text |Cite
|
Sign up to set email alerts
|

The East River tidal strait, New York City, New York, a high-nutrient, low-chlorophyll coastal system

Abstract: The East River tidal strait, located between New York Harbor and Western Long Island Sound, is characterized by high suspended silt concentrations with low organic content kept in suspension by intense tidal currents. Inorganic nutrients, including nitrate, nitrite, ammonia, and phosphate, were high even during the summer. Dissolved inorganic nitrogen (DIN) concentrations generally were above 20 lM and did not likely limit phytoplankton growth. Despite high nutrient concentrations, median chlorophyll a concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
1
3
1
Order By: Relevance
“…Similarly, temperature is in-phase with water level at semidiurnal timescales, while salinity is out of phase. These findings are consistent with measurements reported by Li et al (2018) from the upper East River, which showed that temperature and DOb are positively correlated with water level, and salinity is negatively correlated with water level.…”
Section: Bottom Observationssupporting
confidence: 93%
See 2 more Smart Citations
“…Similarly, temperature is in-phase with water level at semidiurnal timescales, while salinity is out of phase. These findings are consistent with measurements reported by Li et al (2018) from the upper East River, which showed that temperature and DOb are positively correlated with water level, and salinity is negatively correlated with water level.…”
Section: Bottom Observationssupporting
confidence: 93%
“…These findings suggest that surface biological production was higher in 2021 despite lower daily solar irradiance, which may suggest higher nutrient concentrations in 2021. Li et al (2018) also found evidence of diel-cycling DO in the upper East River, however the amplitude of diel fluctuations was an order of magnitude smaller than fluctuations shown here at EXRK likely due to high turbidity in the upper East River which limits production.…”
Section: Surface Observationscontrasting
confidence: 46%
See 1 more Smart Citation
“…The location was unusual in that nutrients remained primarily in the dissolved form over the summer months, and chlorophyll remained low throughout the time series, ranging from 0.95–4.58 with mean 1.67 (Figure S3). Experiments reported in Li et al indicated that growth of local phytoplankton assemblages was light-limited due to persistent high concentrations of PIM in the Bronx River Estuary. Kim et al report rapid onset of light limitation below 0.5 m depth at the same location, with rapid growth of the cultivated macroalgal species Gracilaria tikvahiae only in the uppermost portion of the water column.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, polymer type had the least significant effect on community composition at the SH site, which had the lowest salinity (26 PSU) and is historically characterised by high nutrient loadings (Gobler et al, 2008). Meanwhile, MAR site samples exhibited the most significant effect of polymer type on community composition despite having high nutrient loads and high salinity (Li et al, 2018; Taillie et al, 2020). In general, polymer‐specific influence on plastisphere community composition across previous studies is inconsistent.…”
Section: Discussionmentioning
confidence: 99%